Prevalence and socio-demographic determinants of gynecological morbidity among ever married women of reproductive age group in field practice area of Navodaya Medical College Hospital and Research Centre, Raichur - N. K., Brunda; Kalasker, Pavan; Kurre, Bhaskar (International Journal Of Community Medicine And Public Health, 2018)
Background: India has made rapid progress in social, economy and health sectors since independence and simultaneous dramatic changes in lifestyle and social roles for women, mortality rates have shifted, resulting in a decreasing advantage for women. Explaining the consequences of these dynamic changes requires understanding of the various health effects. In the future these changes will have significant impact on women’s health. Methods: A cross-sectional study was conducted among 400 ever married women of reproductive age group (15-49 years) residing in the urban field practice area of NMCH&RC. Study subjects were interviewed about gynecological morbidities experienced in the recent past 6 months. Blood samples were collected and hemoglobin estimation was done. Results: Out of the total 400 ever married women of reproductive age group (15-49 years), 153 women were found to have gynecological morbidity and the prevalence was found to be 38.3%. Statistically significant association was found among the prevalence of gynecological morbidity and variables like literacy status, occupation, age at marriage, age at menarche and type of family of respondents. Conclusions: Due to the traditional and social constrains, socio-cultural factors of study participants, limit their access to the health care and social support services, thereby providing an environment conducive to acquiring and transmitting RTI/STIs.